Evaluation of the energy saving potential in electric motors applying a load-based voltage control method (2024)
This paper studies the viability of energy savings in electric motors by adjusting the voltage according to load in motors that operate under significant load variations during their work cycles. The laboratory test program used a 1.1 kW electric motor to compare its measured efficiency operating without voltage control with the load-based voltage control method results. A neural network was developed, and a time series generator was used to model the motor and estimate the results of applying the method in its useful life in the load behavior of three operating regimes. The results show an energy saving potential of 2 %–5.2 % using the load-based voltage control method in motors operating with a load factor of less than 40 % during the simulated motor life cycle for the three operating regimes. Also, the economic feasibility of implementing the load-based voltage control method was evaluated on three industrial electric motors. Results indicated potential annual savings between $1227 and USD 1,549, with a projected investment payback period of less than three and a half years.